FEASIBILITY ANALYSIS OF E-GOVERNMENT SERVICES USING TELOS METHOD - Nurfitria Ningsi; Muhammad Nuzul (STMIK Royal, 2023)
Abstract: The government continues to adopt various technologies to ensure effective and efficient public services in the new normal era. This study discusses the use of the TELOS method in measuring the feasibility level of e-government services through a review of five main feasibility dimensions, including technical feasibility, economic feasibility, legal feasibility, operational feasibility and schedule feasibility. This study identifies opportunities for developing village information system projects. The data collection process involved 15 users of e-government services. The results of this study indicate that based on the number of feasibility factors generated by the information system, it is 7.20 and is within the feasible threshold for development. The value of the system development risk obtained is quite low. It is necessary to add interactive features so that it can increase community participation in community services in the future. Keywords: e-Government; feasibility Analysis; TELOS method; Abstrak: Berbagai adopsi teknologi terus dilakukan pemerintah untuk menjamin pelayanan publik yang efektif dan efisien di era normal baru. studi ini membahas tentang Penggunaan Metode TELOS dalam pengukuran tingkat Kelayakan layanan e-government melalui peninjauan lima dimensi kelayakan utama antara lain kelayakan teknis, kelayakan ekonomis, kelayakan hukum, kelayakan operasional dan kelayakan jadwal. Studi ini mengidentifikasi peluang pengembangan proyek sistem informasi desa. Proses Pengumpulan data melibatkan 15 pengguna layanan e-government. Hasil penelitian ini menunjukan bahwa berdasarkan jumlah factor kelayakan yang dihasilkan sistem informasi tersebut sebesar 7,20 dan berada dalam ambang batas layak untuk dikembangkan. Nilai resiko pengembangan sistem yang diperoleh cukup rendah sehingga perlu adanya penambahan fitur-fitur yang bersifat interaktif untuk dapat meningkatkan partisipasi masyarakat terhadap layanan kemasyarakatan dimasa mendatang. Kata kunci: Analisis Kelayakan; e-Government; Metode TELOS